1975
DOI: 10.1021/jm00238a027
|View full text |Cite
|
Sign up to set email alerts
|

.beta.-Aminocinnamonitriles as potential antiinflammatory agents

Abstract: A number of beta-aminocinnamonitriles have been prepared by the reaction of salts of acetonitrile and propionitrile with benzonitrile. These materials were evaluated in the carrageenan antiinflammatory screen in Royal Hart, Wistar strain rats. Despite good weight gains in the parent molecule, beta-aminocinnamonitrile (1), only marginal activity was found in related compounds and some possible "metabolites."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The percent conversion of nitrile was examined in a temperature range of 60-140 C (entry 6,[12][13][14], and the temperature of 120 C was determined as standard condition according to the transformation efficiency of compound 2a. Lower temperature would decrease the yield dramatically down to 3% at 60 C (entry 12), and higher temperature might not help to improve the efficiency of production (entry 14).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percent conversion of nitrile was examined in a temperature range of 60-140 C (entry 6,[12][13][14], and the temperature of 120 C was determined as standard condition according to the transformation efficiency of compound 2a. Lower temperature would decrease the yield dramatically down to 3% at 60 C (entry 12), and higher temperature might not help to improve the efficiency of production (entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…In our lab, the reactions run smoothly with four typical type of 4-amidinopyrimidines and the products were obtained in yields over 76%. All the compounds were characterized by 1 H NMR, 13 C NMR, mass spectra and X-ray crystallography (Fig. 2).…”
Section: Rsc Advances Papermentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that the cyanomethyl anion, generated from acetonitrile by treatment with sodium amide in liquid ammonia and which, to some extent, models the fragment of dianion 1 2-that bears the main part of the negative charge (compare with the charge distribution in the dianion of 9-cyanoanthracene [26] ), reacts with 2 to give β-aminocinnamonitrile (11). [29,30] This result shows that the carbanion adds to the cyano group of 2 and suggests that the interaction of dianion 1 2-with an aromatic nitrile proceeds through a mechanism that is different from that typical for α-cyano-substituted carbanions (see Scheme 2). On this basis, while considering the mechanism of the interaction of dianion 1 2-with aromatic nitriles within the dichotomy between straight nucleophilic attack, on the one hand, and electron transfer (ET), on the other, the latter seems preferable.…”
Section: Resultsmentioning
confidence: 99%